Ambulatory Surgical Services Provided Under California Workers’ Compensation - Barbara O. Wynn, John P. Caloyeras,etc (RAND Corporation, 2014)
The Division of Workers’ Compensation in the Department of Industrial Relations (DIR) maintains an Official Medical Fee Schedule (OMFS) for medical services provided under California’s workers compensation (WC) program. The OMFS establishes the maximum allowable fee for services furnished to injured workers unless the payer and provider contract for a different payment amount. The OMFS allows facility fees for surgical procedures that are furnished in freestanding ambulatory surgical centers (ASCs). To receive an OMFS facility fee, an ASC must either be licensed by the California Department of Public Health, accredited by an accrediting body recognized by the Medical Board of California, or approved for participation in the Medicare program. ASC allowances are based on the Medicare fee schedule for hospital outpatient services.